The Influence of Virtual Reality Applications on the Quality of Education in Medical Colleges (Comprehensive Journal of Science, 2025)
The review article assesses the effect of virtual reality applications on Neurocognitive and practical learning consequences in medical colleges. The traditional teaching methods used in medical education often do not achieve the maximum level of perception and skill acquisition, which is why technologies of VR have appeared just as an innovative instrument which provides immersive, interactive, and realistic learning experiences. Through a thorough study of publications between 2015 and 2024, this paper outlines the main advantages of VR technology: improving knowledge retention, increasing motivation among students, better visualization of complex anatomical structures, and safer simulation of clinical procedures as described in case studies that demonstrate how VR effectively bridges the gap between theoretical instruction and real-world practice in medicine with significant improvements to student confidence and performance. Challenges such as high implementation costs, technical limitations, and inadequate faculty training hinder widespread adoption. It will be concluded here that VR has great potential for future medical education if strategic integration into faculty development and infrastructure sustainability can be achieved. Future research should create standardized frameworks for VR curricula and assesses its long-term impacts on professional competence and patient outcomes.
Keywords: Virtual Reality, Medical Education, Cognitive Learning, Skill Acquisition, Simulation, Educational Technology